Diseminasi Briket Ramah Lingkungan sebagai Solusi dari Limbah Sekam Padi - Dian Kusuma Wardani; Hidayatur Rohmah; Bekti Widyaningsih; Amrini Shofiyani (Lembaga Pengembangan Kinerja Dosen, 2025)
The majority of people in Balongsari Village, Megaluh District, Jombang Regency work as farmers. The rice harvest every harvest period produces very abundant agricultural waste. One of these agricultural wastes is rice husks. A common habit of farmers in this area is burning rice husks. This has an impact on environmental pollution, which comes from the smoke from burning rice husks. The purpose of this activity is to provide a solution for managing rice husk waste so that it is more useful. Proper processing of agricultural waste, namely rice husks, will produce various processed products, namely alternative fuel sources to replace kerosene or LPG gas or firewood. The objects of community service activities are youth of Karang Taruna and farmer groups. The results of this service activity are (1) Obtaining alternatives to replace fuel oil, (2) Reducing rice husk waste, (3) Providing added value to rice husks so that they become more useful. During the activity, participants were very enthusiastic about participating in the event from beginning to end, as evidenced by the results of the questionnaire after the activity, namely 90% of participants were very enthusiastic.